Does sustainability practices of human resources as a new approach able to increase the workers productivity in the SME sector through human resources policy support? - Yus Kelana, Beni Widarman (American Scientific Publishers, 2015)
This article was published to review the key features of sustainability practices in human resources, a number of terms that connects the relationship between sustainability and human resources. Besides that, this article aims to identify whether the proposed approach of five human resource sustainability practices found in the Gollan model17 were able to increase the productivity among workers in the SME sector through human resources policy support so that the organization can gain short and long term benefits. In this case, several sustainability practices of human resources have been considered important in creating an atmosphere of human resources sustainability in an organization to increase labor productivity through participation and consultation of employees, career development and organizational learning, organizational change, work-life balance and institutional systems and workplace. However, human resources policy support is also seen as important in ensuring an effective implementation of sustainability practices of human resources in the workplace. This article also aims to provide debates from previous research in the human resources management field which covers issues of sustainability, implementation of human resources sustainability, human resources policy and to propose a conceptual framework draft for future research.